Different genotypes regulate the microbial community structure in the soybean rhizosphere - Zheng QU; Yue-han LI; Wei-hui XU; Wen-jing CHEN; Yun-long HU; Zhi-gang WANG (Journal of Integrative Agriculture, 2023)
The soybean rhizosphere has a specific microbial community, but the differences in microbial community structure between different soybean genotypes have not been explained. The present study analyzed the structure of the rhizosphere microbial community in three soybean genotypes. Differences in rhizosphere microbial communities between different soybean genotypes were verified using diversity testing and community composition, and each genotype had a specific rhizosphere microbial community composition. Co-occurrence network analysis found that different genotype plant hosts had different rhizosphere microbial networks. The relationship between rhizobia and rhizosphere microorganisms in the network also exhibited significant differences between different genotype plant hosts. The ecological function prediction found that different genotypes of soybean recruited the specific rhizosphere microbial community. These results demonstrated that soybean genotype regulated rhizosphere microbial community structure differences. The study provides a reference and theoretical support for developing soybean microbial inoculum in the future.